A PRPH splice-donor variant associates with reduced sural nerve amplitude and risk of peripheral neuropathy - Gyda Bjornsdottir (Nature Portfolio, 2019)
Diagnosis and classification of peripheral neuropathy (PN) is facilitated by nerve conduction (NC) studies. Here, Bjornsdottir et al. find a low-frequency PRPH splice-donor variant that associates with NC amplitude and neurological assessment of recalled PRPH variant carriers reveals increased risk of a mild sensory-negative PN.